Evaluasi Rating dan Online Customer Review terhadap Keputusan Pembelian Pengguna Shopee - Mochamad Husein Isnaeini; Hani Hasanah; Verawati Fajrin (Universitas 45 Surabaya, 2024)
This study aims to evaluate ratings and online customer reviews on shopee users' purchasing decisions. The population used in this study were all users of the Indonesian shopee marketplace using a sample of 120 shopee users. The respondent selection technique in this study used a non-probability sampling technique with an incidental sampling type. Data collection in this study used a digital questionnaire (google form). This study used a quantitative method with data analysis techniques for convergent validity tests, reliability tests, discriminant validity tests, multicollinearity tests, r-square tests, and hypothesis tests. The results of this study indicate that ratings have a significant effect on purchasing decisions of 6.508> Zscore 1.96 and online customer reviews have a significant effect on purchasing decisions of 16.615> Zscore 1.96. The r-square test shows that ratings and online customer reviews simultaneously influence purchasing decisions by 88.1%.